We considered mutual inductance in my lectures and the definition $M=k\sqrt{L_1L_2}$ where the coupling constant $k$ can vary between 0 and 1. When covering transformers, my lecture notes "assume that all of the flux couples to both coils, such that the coupling coefficient is equal to unity". However I am not sure how this is the case, unless also the self inductance of each coil is the same (which certainly is not the case in the rest of my notes!).

In particular, the flux through each coil is

$$\phi_1 = L_1I_1 + MI_2 = L_1I_1 + k\sqrt{L_1L_2}I_2$$


$$\phi_2 = L_2I_2 + k\sqrt{L_1L_2}I_1$$

Equating these and rearranging, I find that

$$\sqrt{\frac{L_1}{L_2}}I_1 + \sqrt{\frac{L_2}{L_1}}I_2 = (I_1-I_2)k$$

so $$k=1 \iff L_1=L_2$$

Have I misunderstood what it means for 'all of the flux to couple to both coils'?

  • 5
    $\begingroup$ Possible duplicate of How do I show for an ideal transformer $M^2=L_1L_2$? $\endgroup$ Commented Jan 2, 2018 at 19:55
  • $\begingroup$ I think you must be asking if your last equation contradicts $k=1$ for $L_1=L_2$. It does, because you have an incorrect sign in it. $\endgroup$ Commented Jan 2, 2018 at 19:59
  • 1
    $\begingroup$ I really don't see why people think this is a duplicate; it clearly isn't. The linked question asks for a proof that $M=\sqrt{L_1L_2}$ given equal fluxes; this question asks a very specific question about the inner workings of that proof, that's not addressed in the linked thread. $\endgroup$ Commented Jan 3, 2018 at 19:19

1 Answer 1


You are making two errors. First, you cannot equate $\phi_1$ and $\phi_2$ because those are the flux linkages not the flux in the core (the flux linkage is the flux in the core multiplied by the turns number of a coil); second, even assuming that $\phi_1$ and $\phi_2$ can be equated, your conclusion would be incorrect.

So, let's start with the right equations and see what we can obtain.

Let $\lambda_1=N_1\phi$ and $\lambda_2=N_2\phi$ be the flux linkages, $\phi$ being the flux in the core, and $N_1$ and $N_2$ the turns numbers of the two windings.


$$\lambda_1=N_1\phi = L_1i_1 + k\sqrt{L_1L_2}i_2$$


$$\lambda_2=N_2\phi = L_2i_2 + k\sqrt{L_1L_2}i_1.$$

By equating $\phi$ from the equations above and setting $k=1$ we get

$$\frac{L_1i_1 + \sqrt{L_1L_2}i_2}{N_1} = \frac{L_2i_2 + \sqrt{L_1L_2}i_1}{N_2}$$

from which

$$\frac{L_1}{N_1}\left(i_1+\sqrt{\frac{L_2}{L_1}}i_2\right) = \frac{\sqrt{L_1L_2}}{N_2}\left(i_1+\sqrt{\frac{L_2}{L_1}}i_2\right).$$

Cancellation of the two equal terms on both sides yields


That is, when $k=1$, the ratio of the two inductances equals the turns ratio squared.

Furthermore, recalling that the voltages across the windings are the derivatives of the flux linkages, with $k=1$ we get

$$v_1 = \frac{\mathrm{d}\lambda_1}{\mathrm{d}t} = L_1 \frac{\mathrm{d}}{\mathrm{d}t}\left(i_1+\sqrt{\frac{L_2}{L_1}}i_2\right)$$


$$v_2 = \frac{\mathrm{d}\lambda_2}{\mathrm{d}t} = \sqrt{L_1L_2} \frac{\mathrm{d}}{\mathrm{d}t}\left(i_1+\sqrt{\frac{L_2}{L_1}}i_2\right).$$

Taking the ratio of the last two equations yields

$$\frac{v_2}{v_1} = \sqrt{\frac{L_2}{L_1}}=\frac{N_2}{N_1},$$

which is the well-known formula relating the voltage ratio in an ideal transformer.

Finally, take the equation

$$v_1 = L_1 \frac{\mathrm{d}}{\mathrm{d}t}\left(i_1+\sqrt{\frac{L_2}{L_1}}i_2\right)$$

and divide both sides by $L_1$ getting

$$\frac{v_1}{L_1} = \frac{\mathrm{d}}{\mathrm{d}t}\left(i_1+\sqrt{\frac{L_2}{L_1}}i_2\right).$$

Now let $L_1$ tend to infinity; the above equation yields

$$\frac{\mathrm{d}}{\mathrm{d}t}\left(i_1+\sqrt{\frac{L_2}{L_1}}i_2\right) = 0$$



If this constant is initially zero (zero initial flux linkage), the above equation reduces to

$$i_1 = -\sqrt{\frac{L_2}{L_1}}i_2 = -\frac{N_2}{N_1}i_2,$$

which is the second constitutive equation of the ideal transformer.

The answer to your titular question is thus: yes, a unit coupling coefficient is compatible with different self-inductances; as you can see from the derivations above, the consequences of $k=1$ are that i) the ratio of the two inductances equals the turns ratio squared and that ii) the voltage ratio equals the turns ratio.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.